Why Become a PE Teacher? – Motivation, Self-Concept and Implications for Teacher Education - Zoglowek, Herbert (Revija za elementarno izobraževanje, 2021)
Career choice can be seen as a complex decision-making process. Individual interests and goals, subjective assessment of abilities, as well as external requirements and circumstances play important roles. The PE teacher profession is often seen as a fun profession, without special requirements or burdens – an opportunity to turn a hobby into a profession. PE teacher candidates are confronted with the question of why they want to become PE teachers. The results of the survey highlight the importance of “biographical competence”, which must be seen as an important argument for increased attention to the development of the professional self in the PE teacher training program.
Keywords: choice of study, professional self, biographical competence, qualitative approach, didactic implications